Cambridge English First 3 with answers. Authentic Examination Papers (Cambridge, Cambridge University Press, 2018)
This collection of four complete practice tests comprises papers from the Cambridge English: First (FCE) examination; students can practise these tests on their own or with the help of a teacher.The Cambridge English: First examination is part of a suite of general English examinations produced by Cambridge English Language Assessment. This suite consists of five examinations that have similar characteristics but are designed for different levels of English language ability. Within the five levels, Cambridge English: First is at Level B2 in the Council of Europe’s Common European Framework of Reference for Languages: Learning, teaching, assessment. It has also been accredited by Ofqual, the statutory regulatory authority in England, at Level 1 in the National Qualifications Framework. The Cambridge English: First examination is widely recognised in commerce and industry, and in individual university faculties and other educational institutions.